Modelos de regressão aleatória para característica de crescimento em bovinos da raça guzerá - Ferreira, Jorge Luis; Bresolin, Tiago [UNESP]; Lopes, Fernando Brito; Garcia, José Américo Soares; Nepomuceno, Leandro Lopes; Schmidt, Aline Beatriz; Lobo, Raysildo Barbosa (FapUNIFESP (SciELO), 2017)
The aim of this study was to estimate (co)variance components and genetic parameters from birth to yearling weight (550 days of age) in Guzerá cattle, using random regression models. Data set from animals (male and female) born between 1993 and 2011 belonging to ten farms in seven Brazilian States were used. The best-fit model considering direct and maternal genetic effect and permanent environmental animal effect were adjusted by fourth, third, and second order, respectively, using orthogonal polynomials of Legendre. The higher estimated values of direct heritability were observed in birth (0.88) and yearling weight (0.70). The genetic correlations were moderate to high magnitude, remaining up even with the increase in the ages gap.
Random regression models for growth trait in guzera cattle
Keywords: Beef cattle; Genetic correlations; Heritability; Orthogonal polynomials of legendre